Perlawanan dari tanah pengasingan : Kiai Abbas pesantren Buntet dan bela negara / H. Ahmad Zaini Hasan ; editor A. Helmy Faishal Zaini - AHMAD ZAINI HASAN, H.; Helmy Faishal Zaini (LKIS, 2014)
xxii, 174 hlm. ; 23 cm [3 eks.]